Long term follow up of proximal hypospadias repair-urethral stricture should be excluded in adults who present with epididymo-orchitis - Bhandarkar, Kailas P. (Turk J Urol, 2018)
OBJECTIVE: Epididymo-orchitis (EO) is a well-known complication of urinary tract infections (UTI) in children. This is commonly seen in children who had hypospadias repair or in those who had surgery for anorectal malformation especially when it results in urethral stricture. However EO occurring as a complication of urethral stricture in adults operated for hypospadias in childhood is not well documented in the literature. MATERIAL AND METHODS: This is a retrospective review of four adults who had proximal hypospadias repair in childhood. All four men presented to us with EO. They were thoroughly investigated to rule out presence of urethral stricture. RESULTS: Three patients had urethral stricture of which two responded well to dilatation and one required cystoscopy and visual internal urethrotomy. The fourth patient did not have urethral stricture. EO in this patient is thought to be due to excessive straining during micturition causing reflux into seminal vesicles. CONCLUSION: Urethral stricture should be excluded in any adult who had a hypospadias repair and presents with EO. Urethral strictures after hypospadias surgery respond well to dilatation and to endoscopic urethrotomy.